Pressure dependence of the dissociation of acetic, benzoic, mandelic and succinic acids at 298.15 K - Kumar, Anil (Thermochimica Acta, 2005)
Dissociation constants for acetic, benzoic, mandelic and succinic acids have been measured at 298.15 K as a function of pressure up to 138.8 MPa. The spectrophotometric technique using Bromocresol Green as the optical indicator was employed up to ionic strength of 0.03 mol kg(-1) in aqueous solution. Thermodynamic dissociation constants were calculated with the Davies activity coefficient equation. The pressure dependences of the ionization constants for the weak acids can be described by the equation of Lown, Thirsk and Wynne-Jones, application of which leads to accurate partial molal volume change on ionization, Delta(V) over bar (o) and compressibility change, Delta(K) over bar (o) at 0.1 MPa. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Acetic acid; benzoic acid; dissociation constants; high pressure; mandelic acid; succinic acid